(3fXe GdeYdheGJ aj GdQbGHI hGdJObjbs - (3RjGO YHO GdMejO(B, (3GdPjHIs; (3GdQeMj fVGd eMehO(B, s ((3YeGf(B:s (3OGQ GdeSjQI(B,s, 2011)
(3JcfhdhLjG fXe GdeYdheGJ aj efXeGJ GdCYeGd , JObjb fWe GdeYdheGJ GdeMGSHjI , GdJgOjOGJ h GdCNWGQ GdJj JJYQV dgG CfXeI GdeYdheGJ GdeMGSHjI , GdQbGHI Ydi fXe GdeYdheGJ GdeMGSHjI , eHGOF GdQbGHI Ydi GdfXGe GdeMGSHj , fXGe GdeYdheGJ Ydi OhQI GdeTJQjGJ , GdQbGHI Ydi fXGe GdeNRhf h GdQbGHI YdI fXGe GdehGQO GdHTQjI , GdMGcejI GdeDSSjI h MGcejI JcfhdhLjG GdeYdheGJ eY hLhO CSFdI aj fgGjI cd aUds
Keywords: (3GdQbGHIs; (3eQGLYI GdMSGHGJs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s